Praecox feeling among Polish psychiatrists: a grounded theory study - Szuła, Anastazja; Kołtun, Aleksandra; Moskalewicz, Marcin (Psychiatria Polska, 2024)
Objectives: The study aims to identify the sources and components of the so-called praecox feeling - (PF) from the perspective of Polish psychiatrists who experience it and can verbalize it. Methods: Qualitative analysis based on the grounded theory method, conducted on a set of open-ended...
Online veröffentlicht: 31.12.2024
Gesehen am 11.06.2025